CHARACTERISTICS OF HYPERTENSION PATIENT IN POLYCLINIC DISEASE RSUP H. ADAM MALIK MEDAN TAHUN 2017 - Tinah . (Jurnal Ilmiah Keperawatan, 2019)
Hypertension is persistent or persistent blood pressure that exceeds the normal limit of systolic pressure above 140 mmHg and diastole pressure above 90 mmHg. Hypertension is a global problem because of the prevalence that continues to increase in line with lifestyle changes such as smoking, obesity (diet), physical inactivity. The purpose of this study is to determine the Characteristics of Hypertension Patients in Polyclinic RSUP H.Adam Malik 2017. This study is a descriptive study with sampling techniques by Accidental Sampling by means of data collection by distributing questionnaires to respondents. From the results of the research that has been done on 33 respondents that the majority of respondents are 57-69 years old as many as 16 respondents (48.5%), the majority of high school education as many as 16 respondents (48.5%), the majority of male gender as many as 18 Of respondents (54.5%), the majority suffered a long time of 1-2 years as many as 15 people (45.5%), the majority of entrepreneurs 19 respondents (57.6%), smoking majority of 18 respondents (54.5%) , The majority did not exercise yaiu 28 respondents (84.8%), and the majority of respondents who did not have family history of hypertension were 19 respondents (57.6%). It is therefore expected that hypertensive respondents to better maintain a healthy lifestyle, avoid smoking, drinking alcohol, eating fatty foods, avoiding stress, reducing salt intake, and regular exercise.